Inventarisasi Pondok Pesantren (Wilayah Tengah: Kabupaten Katingan, Pulang Pisau, dan Kapuas): Inventory of Boarding Schools (Central Region: Katingan, Pulang Pisau, and Kapuas) - Mazrur, Mazrur; Qodir, Abdul; Ahmadi, Ahmadi; Jasiah, Jasiah; Kartini, Nurul Hikmah (Anterior Jurnal, 2025)
The need for data related to Islamic boarding schools is needed for various policies that will later be related to the development of Islamic boarding schools. This study aims to inventory Islamic boarding schools in the Katingan, Pulang Pisau, and Kapuas districts in terms of their history, number of students and teachers, availability of facilities and infrastructure, and their learning processes. Using a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study were 20 Islamic Boarding School Leaders/Managers. The results of the study were that from the type of Islamic boarding school, 30% still used the salaf concept and 70% used a combination of modern concepts. There are still Islamic boarding schools that have obstacles such as not having permanent dormitories, inadequate road access, the welfare of educators and education personnel, and a lack of experts in Al-Qur'anic knowledge. Recommendations for related parties are for the Ministry of Religion of Katingan, Pulang Pisau, and Kapuas Districts to intensify monitoring and evaluation and provide information on assistance such as building construction, and others; Educational institutions such as state and private universities should make the location of the Islamic boarding school a place for community service by both lecturers and students.